Surgical Management of Intestinal Obstruction - Prateek Shaparia; Chiraag Hiran S; Vijoy Singh; Honeypalsinh H Maharaul; Mohammad Farooque Dudhwala (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background : Intestinal obstruction is one of the common abdominal emergencies and if not treated anddelayed it may lead to bowel ischemia. Hence diagnosis and management of the patient with intestinalobstruction is one of the most important and challenging step to decrease its morbidity and mortality. Thismortality due to acute intestinal obstruction can be decreased with better understanding of pathophysiology,improvement in diagnostic techniques, fluid and electrolyte correction, much potent antimicrobial hence ourstudy focuses on early diagnosis of obstruction, skill full operative management, proper technique duringsurgery and intensive postoperative treatment and carries grateful results.Aim and Objectives :1. To study the various causes of intestinalobstruction.2. To study the symptomatology of intestinalobstruction.3. To study the various Modalities of treatment(surgical) and also the role of imaging studies in determiningthe etiology and intervention in intestinal obstruction.Conclusion : Through our study we came to the conclusion that men are more commonly involved thanfemales . Plain X-ray abdomen and ultrasonography were important for diagnosing out of which Plain X-rayerect abdomen was almost conclusive in all cases. Where diagnosis was inconclusive an ultrasonographywas carried out. Amongst the causes, Postoperative adhesions are the common cause to produce intestinalobstruction. Intestinal obstruction with tuberculosis intestine are more likely to develop postoperativecomplications, proper anti-tubercular management is necessary to prevent mortality and morbidity. Earlyoperations depending upon the etiology of obstruction are mandatory to avoid perforation, the developmentof peritonitis and systemic sepsis associated with multisystem organ failure. Through our study, Adhesiolysisfollowed by resection and anastomosis were the two procedures which were commonly performed. InPostoperative period, few patients had wound infection followed by would dehiscence, chest infection,septicemia and fecal fistula. Morbidity increased in old age patients and those whose presentation was late